2008
DOI: 10.1021/jf8013519
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biotransformation of Inorganic Selenium by Lactobacillus and Saccharomyces in Lactic Fermentation Process of Yogurt and Kefir

Abstract: The aim of the present study was to characterize, quantify, and compare the different selenium species that are produced when lactic fermentation with two different types of microorganisms, bacteria (Lactobacillus) and yeast (Saccharomyces), take place to produce yogurt and kefir, respectively, and to study the transformation process of these species as a function of time. These two dairy products were chosen for the study because they are highly consumed in different cultures. Moreover, the microorganisms pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 26 publications
2
36
2
Order By: Relevance
“…Besides these studies that confirm the transformation of inorganic selenium to organically bound selenium, there are other studies that prove that, e.g., Lactobacillus bulgaricus is able to reduce selenite to insoluble elemental selenium, electro-dense Se 0 granules, thereby depositing in both the cytoplasm and the extracellular space (Xia et al, 2007). Alzate et al (2008) and Zhang et al (2009) reported as well that at higher selenite concentrations, Se 4 microorganisms are reduced to Se 0 as a result of detoxication mechanisms. Considering the abovementioned facts, it should be stated that further research into the lactate-protein complex must be better specified in terms of representation of various selenium forms that are the result of the culturing of Lactobacillus acidophilus in the presence of selenite.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Besides these studies that confirm the transformation of inorganic selenium to organically bound selenium, there are other studies that prove that, e.g., Lactobacillus bulgaricus is able to reduce selenite to insoluble elemental selenium, electro-dense Se 0 granules, thereby depositing in both the cytoplasm and the extracellular space (Xia et al, 2007). Alzate et al (2008) and Zhang et al (2009) reported as well that at higher selenite concentrations, Se 4 microorganisms are reduced to Se 0 as a result of detoxication mechanisms. Considering the abovementioned facts, it should be stated that further research into the lactate-protein complex must be better specified in terms of representation of various selenium forms that are the result of the culturing of Lactobacillus acidophilus in the presence of selenite.…”
Section: Discussionmentioning
confidence: 86%
“…Based on chemical analysis, they determined selenomethionine as the main selenium component of the total protein. Alzate et al (2008) compared selenium forms that are produced from lactic fermentation with two different types of microorganism, bacteria (Lactobacillus) and yeast (Saccharomyces). While Lactobacillus is responsible for yogurt fermentation, synergy of bacteria and the yeast Saccharomyces causes kefir fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Differing excretion of Se in milk was perhaps the cause of the higher Se concentrations in the blood of kids from the group Se-Y. The higher content of Se in the milk is due to (Calomme et al 1995;Alzate et al 2008). Although Se concentration in the blood was significantly different in individual groups (deficient, optimum and increased Se concentrations in kids' blood were observed), muscle metabolism was not substantially affected.…”
Section: Discussionmentioning
confidence: 91%
“…These authors did not discover the microorganisms to incorporate selenium in the form of selenomethionine into protein. Alzate et al (2008) compared selenium forms that are produced during lactic fermentation with two different types of microorganisms, bacteria -Lactobacillus and yeast -Saccharomyces.…”
Section: Discussionmentioning
confidence: 99%